Student Calling Machine When After School by Whatsapp Text Message - Syaiful Amri; Syahrizal; Khairudin Syah; Azizul (International ABEC, 2022)
Crowds still have the potential to occur during the implementation of 100 percent face-to-face learning. School residents, especially students, still find it difficult to keep their distance from each other and that happens especially when it's time to go home from school. To overcome this condition, schools are moving quickly to find solutions. For example, the education unit made an alternative to prevent crowds. Namely providing a special waiting area for students, chairs lined up in the school hallway. The children sat while waiting for their parents to come pick them up. As soon as the parents arrive, the student is called over the loudspeaker, and so on. However, this method is not effective enough to reduce the crowd. Because at the time of calling the students who were picked up, the officer (teacher picket) was overwhelmed to recognize the parents or guardians of the students who were picking up the call by loudspeaker, due to the large number of students there could also be a change in the person who picked up the previous day.